1987
DOI: 10.1002/tox.2540020406
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ionic solutes on EC50 values measured using the microtox test

Abstract: The Microtox test uses the marine luminescent bacterium, Photobacterium phosphoreum. To provide the organism with osmotic protection, sodium chloride (2.0%) is usually added to freshwater samples before analysis. This procedure is shown to cause a dramatic lowering of measured toxicity where ionic compounds are the major toxicants present. The reason for this is the consequent variation in ionic strength upon addition of NaCl rather than formation of less-toxic chloro complexes. Data are given for the toxicant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 9 publications
3
21
0
1
Order By: Relevance
“…The 2.0% sodium chloride concentration is the lowest concentration in the optimum luminescence range. Other investigators have reported the protective effect of increasing saline concentrations within our optimum range on toxicant EC50 values (27,28). This present study justifies the use of 2% saline (22) for sensitivity reasons.…”
Section: Discussionsupporting
confidence: 83%
“…The 2.0% sodium chloride concentration is the lowest concentration in the optimum luminescence range. Other investigators have reported the protective effect of increasing saline concentrations within our optimum range on toxicant EC50 values (27,28). This present study justifies the use of 2% saline (22) for sensitivity reasons.…”
Section: Discussionsupporting
confidence: 83%
“…A higher effective concentration is interpreted as lower toxicity. Hinwood and McCormick [13] have described the details of the experimental procedure. These authors also indicated that log Γ increases with concentration only up to a certain point beyond which no further increase can be observed.…”
Section: Methodsmentioning
confidence: 99%
“…One of these widely used bioassays is the Microtox R assay, a rapid screening alternative to toxicity tests with higher aquatic organisms, such as fishes and invertebrates, applies the luminiscent bacterium Photobacterium phosphoreum as the test organism [4,5]. Nevertheless, studies concerning metal species toxicity to the luminiscent bacteria are scarce [6][7][8].…”
Section: Introductionmentioning
confidence: 99%